2023
DOI: 10.3847/1538-3881/acea77
|View full text |Cite
|
Sign up to set email alerts
|

Characterizing a World Within the Hot-Neptune Desert: Transit Observations of LTT 9779 b with the Hubble Space Telescope/WFC3

Billy Edwards,
Quentin Changeat,
Angelos Tsiaras
et al.

Abstract: We present an atmospheric analysis of LTT 9779 b, a rare planet situated in the hot-Neptune desert, that has been observed with Hubble Space Telescope (HST)/WFC3 with G102 and G141. The combined transmission spectrum, which covers 0.8–1.6 μm, shows a gradual increase in transit depth with wavelength. Our preferred atmospheric model shows evidence for H2O, CO2, and FeH with a significance of 3.1σ, 2.4σ, and 2.1σ, respectively. In an attempt to constrain the rate of atmospheric escape for this planet, we search … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 132 publications
1
8
1
Order By: Relevance
“…Due to its extreme level of irradiation, LTT 9779 b receives >2500×more flux from its host star than the Earth; it might be expected to be in the process of losing its atmosphere through photoevaporation (Owen & Wu 2013;Owen & Lai 2018). However, like Edwards et al (2023), we find no clear evidence for He absorption in our spectrum.…”
Section: Searching For Tracers Of Atmosphere Escapecontrasting
confidence: 58%
See 3 more Smart Citations
“…Due to its extreme level of irradiation, LTT 9779 b receives >2500×more flux from its host star than the Earth; it might be expected to be in the process of losing its atmosphere through photoevaporation (Owen & Wu 2013;Owen & Lai 2018). However, like Edwards et al (2023), we find no clear evidence for He absorption in our spectrum.…”
Section: Searching For Tracers Of Atmosphere Escapecontrasting
confidence: 58%
“…We do not consider the transit light source effect (TLSE; Rackham et al 2018;Fournier-Tondreau et al 2023;Lim et al 2023) in our retrievals as LTT 9779 is known to be slowly rotating and thus inactive (Jenkins et al 2020). Moreover, Edwards et al (2023) included the TLSE in their HST retrievals but found that it was disfavored over models without the TLSE and resulted in unreasonably high-spot and faculaefilling factors.…”
Section: Atmosphere Modelingmentioning
confidence: 95%
See 2 more Smart Citations
“…Also, the planet has a restricted Jeans parameter Λ = GM p m H /(k B T eq R p ) ≈ 27, a gravitational potential Φ = GM p /R p ≈ 4 × 10 12 erg g −1 , and a Roche lobe filling factor R p /R Roche ≈ 50% (Eggleton 1983). Photoevaporation and/or Roche lobe overflow should be vigorous for a planet so close to its host star with such low ρ p , Λ, Φ, and R Roche (Salz et al 2016;Kubyshkina et al 2018;Caldiroli et al 2022;Edwards et al 2023). In fact, escaping atmospheres have been detected for many Jupiter-and Neptunesized planets with similarly small ρ p , Λ, Φ, and/or R Roche .…”
Section: Introductionmentioning
confidence: 99%